Evaluating the efficacy of inhaled amikacin as an adjunct to intravenous combination therapy (ceftazidime and amikacin) in pediatric cystic fibrosis pulmonary exacerbation - Rakhshan, Amin; Farahbakhsh, Nazanin; Khanbabaee, Ghamartaj; Tabatabaii, Seyed Ahmad; Sadr, Saeed; Hassanzad, Maryam; Sistanizad, Mohammad; Dastan, Farzaneh; Hajipour, Mahmoud; Bahadori, Amir Reza; Mirrahimi, Bahador (Frontiers in Pharmacology, 2023)
Background:Pseudomonas aeruginosa is the most common microorganism found in the sputum culture of Cystic fibrosis (CF) patients causing the pulmonary destruction. Aminoglycosides have a low diffuse rate from lipid membranes, and respiratory system secretions. Regarding the burden of pulmonary exacerbation caused by the pseudomonas aeruginosa in cystic fibrosis patients in the long term and the limited number of clinical trials focused on appropriate treatment strategies, the present study evaluated the concurrent inhaled and intravenous aminoglycoside antibiotics for pulmonary exacerbation caused by the pseudomonas aeruginosa as a safe and effective treatment in children. Method: This study was a blinded, randomized clinical trial phase conducted in a tertiary referral pediatric teaching hospital from May 2021 to May 2022. The patients were randomly allocated to receive intravenously administered ceftazidime and Amikacin alone or with inhaled Amikacin. Forced expiratory volume (FEV1), Amikacin via the level, kidney function tests, audiometry, inflammatory markers (erythrocyte sedimentation rate and C-reactive protein), hospital stay, and bacterial eradication rate were compared in two therapy groups. Results: the average FEV1 has increased by 47% in Neb + group compared to Neb− group following treatment. Hospital stay was lower in Neb + group. No renal toxicity or ototoxicity was observed in both therapy groups. Pseudomonas aeruginosa eradication rate Neb− and Neb + groups were 44% and 69%, respectively (p-value = 0.15). Conclusion: Concurrent inhaled and intravenous Amikacin is safe and effective to treat Pseudomonas aeruginosa exacerbation in CF patients. Moreover, co-delivery antibiotics’ route treatment increased the eradication rate. Although not statistically significant, never the less, it is clinically relevant. The intervention reduced the length of hospitalization in this group. Clinical Trial Registration:clinicaltrials.gov, identifier [IRCT20120415009475N10].